Human dignity: a conception from the Social Doctrine of the Church, reports UN human development and social actors (2019)
The Catholic Church from his social doctrine becomes spokesperson of thosepeople who have not word and through this mission fosters an extraordinarymedium to remember that Catholics have a rich tradition known as “Catholicsocial thought”. It is therefore, that on the basis of the social doctrine of theCatholic Church and the Human Development Reports, the interest of thisdocumentary research seeks understand, demonstrate and create opportunitiesfor discussion about human dignity and wants to shows a way of possibilitiesfor achieving a true Human Development as a whole.